The Effect of Concrete-Pictorial-Abstract (CPA) Approach on Improving Elementary School Students’ Spatial Sense Ability - Putri, Hafiziani Eka; Rahayu, Puji; Muqodas, Idat; Wahyudy, Mukhamad Ady (Universitas Pendidikan Indonesia, 2020)
The spatial sense ability of elementary school students is still low. Concrete-Pictorial-Abstract (CPA) approach is considered able to improve students' spatial sense abilities. This research aims to find out the increase of spatial sense of elementary school students who learned with CPA approach and conventional learning in terms of overall students as well as categories of high, medium, and low Mathematical Prior Ability (MPA). This research uses a quasi-experimental method with pretest and posttest control design in Mathematics subject with the topic of 3D geometry for 131 fifth grade elementary school students in Kotabaru District, Karawang Regency and Cipeundeuy District, Subang Regency. This research was conducted by dividing the students into two groups, namely students who received learning using CPA approach as the experimental group and students who received conventional learning as the control group. Descriptive analysis and inferential analysis results showed that there was an increase of spatial sense in students who learned with CPA approach, which was better than students who received conventional learning. Thus, learning using the CPA approach can improve and develop spatial sense abilities of elementary school students.